ARE THERE THINGS ONLY ARTISTS CAN DO? ARCHIVING THROUGH A TREADMILL - Felice Bonfim, Carolina (Cena, 2021)
This article seeks to share the methods and strategies of the practice-based research project Ninety movements on TECHNOGYM G6508D. The research dissects the act of running in all its dimensions by fragmenting, archiving, incorporating, and highlighting what is unique and personal in each gesture and each way of moving. Ninety movements is a continuation of Carolina Bonfim’s recent artistic practice, which explores the relationship between the body and the archive through a visual-arts approach. Keywords Archive. Body. Embodiment. Methodology. Practice-based Research.